2016
DOI: 10.1039/c6tc00493h
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of copper nitride powders and nanostructured films

Abstract: Powders and thin films of copper nitride, Cu3N, can be synthesised simply from copper(ii) trifluoroacetate, the latter by facile solution processing, resulting in stoichiometric nanostructured semiconducting materials with a band gap of 1.48 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 58 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…In addition, from the diffuse reflectance UV/Vis/NIR spectroscopic data the bandgaps were calculated for these complexes. The bandgap ( E g ) is defined as the intersection point between the energy axis and the line extrapolated from the linear portion of the adsorption edge in a plot of Kubelka‐Munk function F against energy E , . As shown in Figure S5, the E g values evaluated from the steep absorption edge are 2.57 and 2.59 eV, respectively, which demonstrates that these complexes are potential semiconductor materials …”
Section: Resultsmentioning
confidence: 90%
“…In addition, from the diffuse reflectance UV/Vis/NIR spectroscopic data the bandgaps were calculated for these complexes. The bandgap ( E g ) is defined as the intersection point between the energy axis and the line extrapolated from the linear portion of the adsorption edge in a plot of Kubelka‐Munk function F against energy E , . As shown in Figure S5, the E g values evaluated from the steep absorption edge are 2.57 and 2.59 eV, respectively, which demonstrates that these complexes are potential semiconductor materials …”
Section: Resultsmentioning
confidence: 90%
“…It is thus expected that copper nitride will react easily with atomic hydrogen. If a thin Cu 3 N layer covered the Cu surface, Cu hydride was proposed to be formed via the following reactionThe formation enthalpies for Cu 3 N, H, and CuH are known to be 74.5, 38 472, and 27.5 kJ/mol, 39 respectively. Although the entropies for Cu 3 N and CuH are unfortunately unknown, given that the entropies for Cu 3 N and CuH are equal to that for CuO, the reaction in eq 4 would be possible below 1000 °C in the presence of atomic hydrogen.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Few reports have demonstrated that Cu 3 N NPs can be synthesized by employing ammonolysis or use of N sources such as azide, hexamethylenetetramine and urea but the challenge with these methods is that the resultant NPs are ill-shaped. [2][3][4][5][6][7][8] Special attention is recently being given to the synthesis of Cu 3 N NPs using direct thermal decomposition of Cu(NO 3 ) 2 $3H 2 O in octadecylamine (ODA) to obtain well dened nanocubes. [9][10][11][12][13] Thermal decomposition of other metal nitrates for example, Mn(NO 3 ) 2 , Ni(NO 3 ) 2 $6H 2 O, Zn(NO 3 ) 2 -$6H 2 O, Ce(NO 3 ) 3 $6H 2 O, Co(NO 3 ) 2 $6H 2 O in ODA resulted in the formation of corresponding metal oxides and not metal nitrides.…”
Section: Introductionmentioning
confidence: 99%